Fostering Students’ Critical Thinking in Islamic Religious Education: A Qualitative Descriptive Study of Teachers’ Practices - Mutholib, Abdul; Gürel, Irmak Sude (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
The development of students’ critical thinking has become an increasingly important concern in Islamic Religious Education (IRE), as religious learning is expected to support reflective reasoning and ethical judgment grounded in Islamic values. Numerous studies emphasize the importance of integrating critical thinking into IRE; however, much of the existing literature remains conceptual or policy-oriented. Empirical evidence documenting how teachers enact critical thinking through everyday classroom practices, particularly based on qualitative classroom observations, remains limited. In this study, critical thinking is defined as students’ capacity to analyze, interpret, evaluate, and reflect on religious concepts and real-life issues. Higher-order thinking skills (HOTS) are conceptualized as pedagogical and assessment-oriented strategies employed by teachers to facilitate this cognitive process. Accordingly, this study aims to explore how Islamic Religious Education teachers foster students’ critical thinking through the integration of HOTS-oriented instructional strategies in classroom practice using a qualitative descriptive design. This study is limited to a specific institutional context and focuses on teachers’ instructional practices rather than quantitatively measuring students’ learning outcomes. However, it offers empirical insight into classroom-level implementation of critical thinking in IRE and contributes practical guidance for educators seeking to integrate HOTS while preserving the moral and spiritual objectives of Islamic education.